To solve the equation 12 = 36/y using substitution, we can first isolate the variable y in one of the equations and then substitute that expression into the other equation.
Given equation: 12 = 36/y
Step 1: Isolate y
Multiply both sides of the equation by y to get rid of the fraction:
12y = 36
Step 2: Substitute
Take the expression for y from step 1 (12y = 36) and substitute it into the other equation.
12 = (36/y)
Replace y in the equation with (36/y):
12 = (36/(12))
Step 3: Solve
Simplify the right side of the equation:
12 = 3
Since 12 does not equal 3, this equation has no solution.
Therefore, the equation 12 = 36/y has no solution.
Slove the equation 12 = 36/y using substitution
3 answers
Give the closest answer
Apologies for the incorrect answer in the previous response. Let's solve the equation correctly:
To solve the equation 12 = 36/y using substitution, we need to isolate y.
Step 1: Isolate y
Multiply both sides of the equation by y to get rid of the fraction:
12y = 36
Step 2: Solve for y
Divide both sides of the equation by 12 to solve for y:
y = 36/12
y = 3
So, the solution to the equation 12 = 36/y is y = 3.
To solve the equation 12 = 36/y using substitution, we need to isolate y.
Step 1: Isolate y
Multiply both sides of the equation by y to get rid of the fraction:
12y = 36
Step 2: Solve for y
Divide both sides of the equation by 12 to solve for y:
y = 36/12
y = 3
So, the solution to the equation 12 = 36/y is y = 3.